The Meaning of hatha in Early Hathayoga - Birch, J (2011)
This essay was prompted by the question of how Hathayoga, literally 'the Yoga of force', acquired its name. Many Indian and Western scholars have understood the 'force' of Hathayoga to refer to the effort required to practice it. Inherent in this understanding is the assumption that Hathayoga techniques such as pranayama (breath control) are strenuous and may even cause pain. Others eschew the notion of force altogether and favor the so-called 'esoteric' definition of Hathayoga (i.e, the union of the sun (ha) and moon (ṭha) in the body). This essay examines these interpretations in light of definitions of hathayoga and the adverbial uses of hatha (i.e, hathat, hathena) in Sanskrit Yoga texts that predate the fifteenth-century Hathapradipika.